2020
DOI: 10.1177/0956797619900321
|View full text |Cite
|
Sign up to set email alerts
|

What We Owe to Family: The Impact of Special Obligations on Moral Judgment

Abstract: Although people often recognize the moral value of impartial behavior (i.e., not favoring specific individuals), it is unclear when, if ever, people recognize the moral value of partiality. The current studies investigated whether information about special obligations to specific individuals, particularly kin, is integrated into moral judgments. In Studies 1 and 2, agents who helped a stranger were judged as more morally good and trustworthy than those who helped kin, but agents who helped a stranger, instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 40 publications
11
106
1
Order By: Relevance
“…If observers infer greater selfish motivations for actors' behavior when it signals more attractive traits, then generosity's being more attractive than impartiality to potential interaction partners may account for our results. It would not be surprising if the strength of social norms and the attractiveness of interaction partner traits were correlated, though there might also be interesting moderators of this association, such as relational obligations (McManus, Kleiman-Weiner, & Young, 2020). There might be interesting cases where These explanations are neither mutually exclusive nor exhaustive, and future work may dissociate their contributions to differential virtue discounting across generosity and impartiality, and other virtues (Graham et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…If observers infer greater selfish motivations for actors' behavior when it signals more attractive traits, then generosity's being more attractive than impartiality to potential interaction partners may account for our results. It would not be surprising if the strength of social norms and the attractiveness of interaction partner traits were correlated, though there might also be interesting moderators of this association, such as relational obligations (McManus, Kleiman-Weiner, & Young, 2020). There might be interesting cases where These explanations are neither mutually exclusive nor exhaustive, and future work may dissociate their contributions to differential virtue discounting across generosity and impartiality, and other virtues (Graham et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, side-taking is an essential part of being a good friend, and research has shown that people react negatively towards a friend who remains neutral as much as towards a friend who is against them (Shaw, DeScioli, Barakzai, & Kurzban, 2017). Additionally, agents who helped strangers instead of kin are judged as less morally good and trustworthy (McManus, Kleiman-Weiner, & Young, 2020).…”
Section: Egocentric Evaluations Are Strategicmentioning
confidence: 99%
“…For instance, an evidence-based belief may be morally bad because it constitutes a form of disloyalty towards one's friends or family (of whom one is supposed to think well; c.f. Cohen & Rozin, 2001;Keller, 2004;McManus, Kleiman-Weiner, & Young, 2020;Stroud, 2006). Alternatively, as some philosophers have argued, making race-or sex-based inferences may fail to treat minorities with due respect, even when they are based on evidence (e.g., Basu, 2019; but see Gardiner, 2018).…”
Section: The Case For Moral Encroachment On Belief Evaluationmentioning
confidence: 99%